Kalam Khabar dan, Insyai dalam Do’a Nabi Zakariyah pada Surah Maryam Ayat 4,5,6,7,8,10,11: Studi Analisis Balaghah - Nurfadillah Winata Zendrato; Muhammad Arif Saman; Fauzan Fahmi; Harun Al Rasyid (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This writing intends to tell the story of the khabar, God willing, in the prayer of the Prophet Zakariyah to Allah SWT which explains the meaning of the Prophet Zakarivah to Allah SWT. This type of research uses quantitative methods with the research object being the dialogue of the Prophet Zakariyah AS. The findings show that there are, in fact, seven verses that contain kalam khabar, and God willing, in the Dialogue of the Prophet Zakariyah in Surah Maryam the use of words in the dialogue is not based on their true meaning because the recipient of the information knows more about the information conveyed. kalam khabar in this dialogue aims to convey information to those who know it. It's the same with kalam ins'ya which shows not the true meaning. because a command in this verse is from bottom to top, the form of the word command in this verse cannot be called a command because the command is from top to bottom, so in this verse it is not an order but in the form of a prayer (request)